65 The novel plasma biomarker desmosine, a marker of elastin breakdown, is an independent predictor of abdominal aortic aneurysm events independent of aneurysm size. (June 2018) - Mordi, Ify; Forsythe, Rachael; Bown, Matthew; Lang, Chim; Newby, David; Gellatly, Corry; Chin, Calvin; McBride, Olivia; Saratzis, Athanasios; Iskandar, Zaid; Chalmers, Rod; Huang, Jeffrey; et al.
Abstract : Abdominal aortic aneurysm (AAA) is the thirteenth leading cause of death and occurs in 5% of men between the ages of 65 and 74 years. Currently, patients at risk for AAA are offered ultrasound screening and surveillance, and when appropriate (size >55 mm or expansion rate >10 mm/year), elective AAA repair. Despite this surveillance, prediction of patients likely to have AAA rupture is difficult, with many AAAs rupturing before reaching 55 mm or having unpredictable expansion rates. A serum biomarker that could predict AAA events would be extremely valuable. Desmosine is an amino acid cross-link that is released into the bloodstream when there is elastin breakdown. We hypothesised that plasma desmosine (pDES) might be associated with events in patients with AAA. Methods: We evaluated pDES levels in 239 patients with AAA recruited to the MA3RS study (NCT01749280 ). Patients had 6 monthly visits with abdominal ultrasound performed at each visit. A panel of biomarkers related to vascular integrity was also obtained. Patients were followed up for clinical events including AAA rupture, repair and mortality. Results: The cohort was predominantly male (87.4%). Mean AAA diameter was 50.6±8.0 mm. pDES was significantly correlated with ultrasound AAA diameter (r=0.27, p<0.0001). In total 13 patients had an emergency AAA event and 20 had MACE (AAA event +CV mortality). pDES was a major predictor of both AAA events (HR 4.97, 95% CI 1.05–23.64, p=0.044) and MACE (HR 5.92, 95% CI 1.73–20.26, p=0.005) independent of AAA diameter, with patients with the highest tertiles of pDES having the worst outcome. pDES was significantly more associated with AAA events than the next best biomarker, MMP-9 (AUC 0.70 vs 0.60, p<0.001). pDES was associated with improvement in risk prediction when added to AAA diameter with a significant improvement in both net reclassification index (p=0.013) and integrative discrimination increment (p<0.001). Conclusion: pDES was an independent predictor of adverse outcome in patients with AAA and may be the first non-invasive serum biomarker to predict events in this group of patients.